Gambaran Kematangan Karir Mahasiswa Tingkat Akhir Universitas Ivet - Khasanah Khasanah; Sri Sayekti (Al-Mudarris, 2020)
The career maturity of graduates determines the success of working according to their education. For this reason, readiness in determining career is very important. This study aims to analyze the career maturity of students. The sample of this study was 102 students of Ivet University who were selected using the Proportionate Stratified Random Sampling technique. Data collection used the Career Development Inventory-Adult scale. The results of the descriptive analysis show that the final semester students have high readiness in facing the world of work, both male and female. The results of the research for indicators towards career readiness are career specifications, career implementation, job crystallization and high-yielding job specifications. Based on the research results, it can be concluded that the final year students of Ivet University are ready to determine the career they choose after graduating.